Varmt hjerte og kaldt blod. En kontrastiv analyse av uttrykk for følelser basert på indre organer og kroppsvæsker i polsk og norsk - Horbowicz, Paulina (Folia Scandinavica Posnaniensia, 2009)
The following paper investigates the nature of idiomatic expressions for emotions and analyses them in Polish and Norwegian. Emotions are a phenomenon universal for all human beings, yet their perception and expression differs across cultures. It seems to be a tendency in all languages to ‘somatize’ emotions, that is to place them in the human body, the nearest reference point. However, explaining this tendency by physiology is not always plausible as shown in the conducted study on expressions using internal organs and bodily liquids in Polish and Norwegian. Expressions that bear most similarity between languages coming from the same culture circle are not those motivated by physiology, but by culture, as for example those originating from Hippocratic humoral doctrine. Metaphorical mechanisms, claimed by some linguists to be universal, for example the so called container metaphor, are also to be found in the analyzed material. It has been proven that culture can influence the construction and perception of emotions. The language of emotions, which by default is a part of culture, calls therefore for more attention from researchers in all fields dealing with this topic.